Assessing the applicability of the European standard EN 17037:2018 for office spaces in a cold climate. (November 2022) - Sepúlveda, Abel; De Luca, Francesco; Varjas, Toivo; Kurnitski, Jarek
Abstract: There is a lack of methods and studies that evaluate the validity of daylight standards such as the EN 17037:2018 in specific local contexts as cold climates. Moreover, the probable adaptation of the EN 17037:2018 by European countries motivated the aim of this investigation: to study the applicability of the EN 17037:2018 in a certain cultural context through the comparison of the subjective perception of Estonian office users with the quantitative assessment defined by the EN 17037:2018, including the four aspects: solar access, view out, daylight provision, and glare protection. In order to study the applicability of the EN 17037:2018 for Estonian office spaces, we used a mixed-method approach based on semi-structured interviews, measurements, and daylight simulations. Poor view out is related with high obstruction levels of urban features, despite the presence of multiple layers in the view. The level of recommendations for good view out in Estonian office rooms might be lower than the thresholds recommended by the EN 17037:2018. Except during winter months, direct sunlight exposure is not appreciated in Estonian office spaces since it is strongly related to glare discomfort caused by sun in the field of view and on computer screens. Working under daylight conditions during the whole year and having an easy-to-use interior shading systems to block the direct sunlight is very valuable for Estonian office users. For daylight and glare protection, there is a good agreement between qualitative evaluations given by office users and quantitative assessments proposed by the EN 17037:2018. Highlights: Disagreement between subjective and quantitative view out evaluations. Agreement between subjective and quantitative daylight/glare assessments. Poor view out levels were linked to high obstruction levels of urban features. Sunlight exposure was only preferred by Estonian office occupants during winter.